Strategi Pemeliharaan Komponen Kritis Hatch Cover Berbasis Reliability Centered Maintenance (RCM) dalam Mendukung Keandalan Operasional Kapal - Andre Sofian; Erwin Sutantyo; Purwanto Purwanto; Rahindra Bayu Kumara; Widar Bayu Wantoro; Irsat Surya Sekti (Jurnal Maritim Polimarin, 2026)
The hatch cover is an important component on bulk carrier vessels that supports cargo protection and loading-unloading operations. Damage to the hatch cover may disrupt operational activities, increase accident risks, and cause delays in coal distribution. This study aims to analyze hatch cover maintenance and identify critical components with the potential for failure. The research used a mixed-method approach through Reliability Centered Maintenance (RCM). Data were collected through observations, documentation, and questionnaires distributed to ship crews. The analysis methods included Functional Block Diagram (FBD), Failure Mode and Effects Analysis (FMEA), Logic Tree Analysis (LTA), and task selection. The results showed that the hydraulic pipe was the most critical component, with the highest Risk Priority Number (RPN) value of 576 due to leakage causing unstable hydraulic pressure. Other components, such as the hydraulic jack, hatch cover wheels, and chain, also showed significant failure risks affecting hatch cover performance. The recommended maintenance actions include periodic inspections, routine maintenance, and replacement of damaged components. Proper implementation of maintenance is expected to improve hatch cover reliability, operational safety, and the efficiency of bulk carrier operations.